(untitled) (Journal of Science and Technology, 2016)
Studies were carried out on the toxicity of the powders of four botanicals on Periplaneta ameri- cana. The tested plants include: Parquetina nigrescens, Azadirachta indica, Zanthoxylum zanthoxyloides and Eugenia cariophyllus. Each of the plant materials (PM) was pulverized and then applied to the insects in four different doses. The dosage rates were 25%PM+75% biscuit, 50%PM+50%biscuit, 75%PM +25%biscuit and 100% PM+0% biscuit. Mortality of insects was monitored and recorded on daily basis for three days. Three of the tested plants, that is, P ni- grescens, Z zanthoxyloides and E caryophyllus were very effective as mortality of insects treated with all the doses were significantly different P<0.5 from the control from the first day to the third day. The least dose(0.5g) of P nigrescens and Z zanthoxyloides produced mortality of 83.3 % each, at the end of the second day of application. The same dose of E caryphyllus produced 100% at 2 days post treatment. Higher doses of these three plants produced 100% mortalitic on the second and third day. However, for experiments involving A indica, only the highest dose of 100% PM gave a significantly high mortality rate when compared with the control.